Ecological function over evolutionary legacy: The limited role of shared evolutionary history in shaping modern frugivory interactions - Fuzessy, Lisieux [UNESP]; Verdú, Miguel; Pizo, Marco Aurelio [UNESP] (Wiley, 2025)
Abstract Frugivory, encompassing interactions between vertebrates and plants that range from mutualistic to antagonistic, drives seed dispersal and underpins the structure and resilience of tropical ecosystems. However, the relative importance of shared evolutionary history versus present‐day functional traits in shaping these interactions remains unresolved. Here, we analyse frugivory networks involving bats, birds and primates across the Neotropics through a comprehensive framework that evaluates the interplay between evolutionary constraints and ecological sorting in mutualistic networks. Using the Procrustean Approach to Cophylogeny, we detect a weak but significant cophylogenetic signal, suggesting that evolutionary history leaves a detectable, though limited, imprint on network structure. In contrast, ecological and functional traits—particularly dietary specialization, network connectivity and fruit characteristics such as husk presence, type, colour and size—emerge as dominant drivers of interaction patterns. Species with similar ecological roles tend to cluster within modules, especially among primates and bats, reflecting strong trait‐mediated filtering rather than phylogenetic conservatism. Moreover, we document contrasting evolutionary patterns between interaction partners, as vertebrate traits exhibit strong phylogenetic signal, while fruit traits are more evolutionarily labile, indicating that plant traits may respond more rapidly to ecological pressures. These findings suggest that evolutionary legacy provides a scaffold for frugivory interactions, but contemporary ecological processes more strongly shape their assembly and modular structure. This asymmetry challenges assumptions about strict coevolutionary matching and highlights the flexibility of plant–animal interactions under ecological change. The framework offers a roadmap for disentangling drivers of interaction patterns in other mutualisms, with broad applications to community ecology, trait evolution, and conservation biology. Understanding how trait matching, often influenced by conserved traits, and shared evolutionary history interact to structure mutualistic networks is essential for predicting their resilience under global change, emphasizing the need to conserve not only species but also the interactions that sustain tropical biodiversity and ecosystem functioning. Read the free Plain Language Summary for this article on the Journal blog. Resumo A frugivoria, que abrange interações entre vertebrados e plantas que variam do mutualismo ao antagonismo, impulsiona a dispersão de sementes e sustenta a estrutura e a resiliência dos ecossistemas tropicais. No entanto, a importância relativa da história evolutiva compartilhada em comparação com os traços funcionais atuais na determinação dessas interações permanece em aberto. Aqui, analisamos redes de frugivoria envolvendo morcegos, aves e primatas em toda a região Neotropical por meio de um arcabouço abrangente que avalia a interação entre restrições evolutivas e filtragem ecológica em redes mutualísticas. Usando a Abordagem Procrusteana para Coevolução (PACo), detectamos um sinal cofilogenético fraco, porém significativo, sugerindo que a história evolutiva deixa uma marca detectável, embora limitada, na estrutura da rede. Em contraste, traços ecológicos e funcionais—particularmente a especialização alimentar, a conectividade na rede e características dos frutos, como presença de casca dura, tipo, cor e tamanho—emergem como os principais determinantes dos padrões de interação. Espécies com papéis ecológicos semelhantes tendem a se agrupar em módulos, especialmente entre primatas e morcegos, refletindo um forte filtro mediado por traços, em vez de conservadorismo filogenético. Além disso, documentamos padrões evolutivos contrastantes entre parceiros de interação: os traços dos vertebrados exibem forte sinal filogenético, enquanto os traços dos frutos são mais evolutivamente lábeis, indicando que os traços das plantas podem responder mais rapidamente às pressões ecológicas. Esses resultados sugerem que a herança evolutiva fornece um arcabouço para as interações de frugivoria, mas que os processos ecológicos contemporâneos moldam de forma mais intensa sua montagem e estrutura modular. Essa assimetria desafia pressupostos sobre um pareamento coevolutivo estrito e ressalta a flexibilidade das interações planta–animal diante de mudanças ecológicas. O arcabouço proposto oferece um guia para desvendar os fatores que determinam padrões de interação em outros mutualismos, com amplas aplicações na ecologia de comunidades, evolução de traços e biologia da conservação. Compreender como o pareamento de traços, muitas vezes influenciado por características conservadas, e a história evolutiva compartilhada interagem para estruturar redes mutualísticas é essencial para prever sua resiliência frente às mudanças globais, enfatizando a necessidade de conservar não apenas as espécies, mas principalmente as interações que sustentam a biodiversidade tropical e o funcionamento dos ecossistemas.